Patient Blood Management: Improving Outcomes for Millions While Saving Billions. What Is Holding It Up?. (17th August 2022) - Hofmann, Axel; Shander, Aryeh; Blumberg, Neil; Hamdorf, Jeffrey M.; Isbister, James P.; Gross, Irwin
Abstract : Patient blood management (PBM) offers significantly improved outcomes for almost all medical and surgical patient populations, pregnant women, and individuals with micronutrient deficiencies, anemia, or bleeding. It holds enormous financial benefits for hospitals and payers, improves performance of health care providers, and supports public authorities to improve population health. Despite this extraordinary combination of benefits, PBM has hardly been noticed in the world of health care. In response, the World Health Organization (WHO) called for its 194 member states, in its recent Policy Brief, to act quickly and decidedly to adopt national PBM policies. To further support the WHO's call to action, this article addresses 3 aspects in more detail. The first is the urgency from a health economic perspective. For many years, growth in health care spending has outpaced overall economic growth, particularly in aging societies. Due to competing economic needs, the continuation of disproportionate growth in health care spending is unsustainable. Therefore, the imperative for health care leaders and policy makers is not only to curb the current spending rate relative to the gross domestic product (GDP) but also to simultaneously improve productivity, quality, safety of patient care, and the health status of populations. Second, while PBM meets these requirements on an exceptional scale, uptake remains slow. Thus, it is vital to identify and understand the impediments to broad implementation. This includes systemic challenges such as the so-called "waste domains" of failure of care delivery caused by malfunctions of health care systems, failure of care coordination, overtreatment, and low-value care. Other impediments more specific to PBM are the misperception of PBM and deeply rooted cultural patterns. Third, understanding how the 3Es—evidence, economics, and ethics—can effectively be used to motivate relevant stakeholders to take on their respective roles and responsibilities and follow the urgent call to implement PBM as a standard of care.